2010
DOI: 10.1037/a0019968
|View full text |Cite
|
Sign up to set email alerts
|

The effects of technical difficulties on learning and attrition during online training.

Abstract: Although online instruction has many potential benefits, technical difficulties are one drawback to the increased use of this medium. A repeated measures design was used to examine the effect that technical difficulties have on learning and attrition from voluntary online training. Adult learners (N = 530) were recruited online and volunteered to participate in a four-hour training program on using computer spreadsheets. Technical difficulties were inserted in some of the training modules in the form of error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 89 publications
(132 reference statements)
2
51
0
1
Order By: Relevance
“…Academics may have to think more creatively, however, about how to integrate digital recordings into a program of study that effectively provides ongoing support to nursing students (Salamonson and Lantz, 2005) in which students remain engaged and feel supported (Shelton, 2003). Student support will necessarily include developing IT skills in this population (Creedy et al, 2007;Sitzmann et al, 2010;Wilkinson et al, 2009) and also guidelines for the best use of digitally recorded lecture material. Digitally recorded lectures can clearly help support students struggling with medical terminology (usage and even pronunciation), revising difficult concepts, reviewing material prior to laboratory exercises or examinations and also support students who might otherwise not have the opportunity to listen to an enhanced and developed presentation of material.…”
Section: Discussionmentioning
confidence: 99%
“…Academics may have to think more creatively, however, about how to integrate digital recordings into a program of study that effectively provides ongoing support to nursing students (Salamonson and Lantz, 2005) in which students remain engaged and feel supported (Shelton, 2003). Student support will necessarily include developing IT skills in this population (Creedy et al, 2007;Sitzmann et al, 2010;Wilkinson et al, 2009) and also guidelines for the best use of digitally recorded lecture material. Digitally recorded lectures can clearly help support students struggling with medical terminology (usage and even pronunciation), revising difficult concepts, reviewing material prior to laboratory exercises or examinations and also support students who might otherwise not have the opportunity to listen to an enhanced and developed presentation of material.…”
Section: Discussionmentioning
confidence: 99%
“…A study of online trainees found that system intrusions (i.e. error messages and network issues) inhibited self-regulation and learning, leading trainees to forget some key declarative and procedural aspects of their training material (Sitzmann et al, 2010). Similarly, actionable intrusions impel individuals to unload parts of their working memories to act upon the interruptions and then resume the interrupted task.…”
Section: Effects Of System Intrusions and Actionable Intrusions On Efmentioning
confidence: 99%
“…Technical difficulties encountered during computer-based or online learning have been found to have a significant negative effect on learning outcomes 25 and on student attitudes. 26 Therefore, this study also aimed to assess whether this was a factor in the effectiveness of the online materials.…”
Section: Introductionmentioning
confidence: 99%